Effect of thermocycling on tensile bond strength of six silicone-based, resilient denture liners - ÖZKAN, YASEMİN (MOSBY-ELSEVIER, 2003)
Statement of problem. Adhesion failure between silicone resilient denture lining materials and denture base resin is commonly encountered in clinical practice. Adhesion failure results in localized unhygienic conditions at the debonded regions and often causes functional failure of the prosthesis. Purpose. The purpose of this study was to investigate the effect of thermocycling on the tensile bond strength of 6 soft lining materials. Material and methods. Six commonly used silicone-based resilient denture liners (Ufigel C, Ufigel P, Mollosil, Molloplast B, Permafix, and Permaflex) were chosen for the investigation. The bond strength was determined, in tension, after processing to PMMA. The resilient denture liners for each group (n = 24) were 10 X 10 X 3 turn and were processed between 2 polymethyl methacrylate specimens according to manufacturer's instructions. Two PMMA specimens were prepared by investing brass dies with a 3-mm-thick spacer in a denture flask. Specimens were made by processing the resilient denture liners against the polymerized PMMA block. After polymerization, the brass spacer was removed from the mold, the 2 PMMA resin specimens were trimmed, and the surfaces to be bonded were smoothed. The PMMA block was placed back into the molds and the resilient denture liners were packed into the space made by brass spacer, trial packed, and polymerized according to the manufacturer's instructions. Half of the specimens for each group were stored in water for 24 hours, and the other half were thermocycled (5000 cycles) between baths of 5degrees and 55degreesC. All specimens were placed under tension until failure in a universal testing machine at a crosshead speed of 5 mm/min. The maximum tensile stress before failure and mode of failure were recorded. The mode of failure was characterized as cohesive, adhesive, or mixed mode, depending on whether the fracture surface was in the soft liner only, at the denture base-soft liner interface only, or in both. Failure strength was recorded in kg/cm(2). Results were tested by multiple analysis of variance (ANOVA) for mode of failure (adhesive, cohesive, and mix), 2-way ANOVA (storage-products), and 1-way ANOVA (storage-products interaction, before and after thermocycling). Duncan's test was used to determine whether significant changes in the tensile bond properties of the materials occurred during thermocycling. Results. Varying degrees of bond strengths were found for soft lining materials and were significantly different (P<.05). Results of this study also indicated that the bond strengths of soft lining materials had significantly decreased after thermocycling except Ufigel C and Mollosil. Conclusions. Because the adequate adhesive value for soft lining materials is given 4.5 kg/cm(2), all of the materials were acceptable for clinical use. (J Prosthet Dent 2003;89:303-10.)
Keywords: LINING MATERIALS; RESIN